Pelatihan Neuro Linguistic Programming (NLP) untuk Meningkatkan Kepercayaan Diri - Zahro, Nur Khumaidatuz (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract This study aims to examine the effectiveness of NLP (Neuro Languistic Programming) training in increasing adolescent self-confidence. This study uses an experimental approach with a quasi-experimental research design. The research subjects were taken by purposive sampling technique with the condition of low self-confidence. The data collection technique used is the confidence scale. Data analysis techniques used in this study used the analysis of independent sample test using Mann-Whitney. The results of the study based on the Independent Sample Test analysis obtained t value of 6.439 with a significance of 0.000 (p <0.05). This shows that the respondents' confidence varies significantly. So it is known that the mean of the experimental group is higher than the control group (36.04> 12.96). This shows that NLP (Neuro Languistic Programming) training is effective significantly to increase the confidence of adolescents who experience self-confidence barriers. Keywords: NLP training, self-confidence, education level